1996
DOI: 10.1021/jp953023m
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Chlorinated Ceria and Chlorine-Containing Reduced Pd/CeO2 Catalysts. A FTIR Study

Abstract: Adsorption of CO, used as infrared molecule probe, was performed at room temperature or at low temperature (140 K), on either chlorine-free or chlorine-containing ceria, in order to investigate both the chlorine effect and the ceria reduction state. On ceria and Pd/ceria catalysts, chlorine acts as an electronegative ligand. Its effect extends to the raft-like structure of palladium in Pd/CeO 2 catalysts. Moreover, ceria chlorination prevents palladium from CO clustering. CO adsorption on the chlorine-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…Chlorine is not known to interact with the electrolyte material, however interactions with ceria, gold, silver, and platinum have been documented. 46 Both gold and platinum form stable chlorides at high temperature, however unlike nickel, these materials do not sublimate under conditions relevant for the studies performed in this work. 42 Chlorine also adsorbs to ceria, affecting catalytic activity and conductivity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chlorine is not known to interact with the electrolyte material, however interactions with ceria, gold, silver, and platinum have been documented. 46 Both gold and platinum form stable chlorides at high temperature, however unlike nickel, these materials do not sublimate under conditions relevant for the studies performed in this work. 42 Chlorine also adsorbs to ceria, affecting catalytic activity and conductivity.…”
Section: Discussionmentioning
confidence: 95%
“…42 Chlorine also adsorbs to ceria, affecting catalytic activity and conductivity. 46 Because none of these processes permanently affect the fuel cell, the high frequency impedance including R bulk recovered fully following removal of CH 3 Cl from the incident fuel feed. The same behavior was not observed for the changes to the polarization arcs observed in the Nyquist plots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the band at 2032 cm -1 may suggest the presence of defect sites which were able to activate the CO molecule on the Cl-free catalyst, these sites being likely candidates to promote the CO oxidation reaction. Badri et al [50] also observed a similar shift in the CO band induced by chlorine species. In agreement with these results, this shift was due to the formation of an active electronegative species by chlorine.…”
Section: Co Prox: Effect Of Feed Compositionmentioning
confidence: 66%
“…Apparently, those oxygen vacancies at the metalsupport interface favor the activation of the CO molecule and provide active sites for the oxidation to CO 2 [49]. On the contrary, in the chlorinated catalyst, chlorine inhibited the formation of those oxygen vacancies due to the formation of CeOCl surface species [22,50,51]. This process was favored at high reduction temperatures.…”
Section: Co Prox: Effect Of Reaction and Reduction Temperaturementioning
confidence: 99%
See 1 more Smart Citation